2022
DOI: 10.1161/circgen.121.003686
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Childhood Cardiomyopathy

Abstract: Background: The causes of cardiomyopathy in children are less well described than in adults. We evaluated the clinical diagnoses and genetic causes of childhood cardiomyopathy and outcomes of cascade genetic testing in family members. Methods: We recruited children from a pediatric cardiology service or genetic heart diseases clinic. We performed Sanger, gene panel, exome or genome sequencing and classified variants for pathogenicity using American Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…While this could be due to asymptomatic patients receiving a diagnosis only during routine check-ups or other illnesses, socioeconomic factors that affect the access of young children/families to healthcare services in the country should not be ignored. Moreover, one another comprehensive study revealed positive association between cardiomyopathy subtype and age at diagnosis(Bagnall et al, 2022). Similarly, the diagnosis of HCM was made at later ages compared to other subtypes, while in cases of DCM, it was made before the age of 3 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…While this could be due to asymptomatic patients receiving a diagnosis only during routine check-ups or other illnesses, socioeconomic factors that affect the access of young children/families to healthcare services in the country should not be ignored. Moreover, one another comprehensive study revealed positive association between cardiomyopathy subtype and age at diagnosis(Bagnall et al, 2022). Similarly, the diagnosis of HCM was made at later ages compared to other subtypes, while in cases of DCM, it was made before the age of 3 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Autosomal dominant variants in TNNT2 are a well-established genetic cause for dilated, hypertrophic, restrictive, or non-compaction CM [6]. However, the clinical phenotype of TNNT2-associated CM shows high variability, as illustrated by an overview of clinically reported variants in TNNT2 [Supplementary Table S1].…”
Section: Discussionmentioning
confidence: 99%
“…For all three variants, the affected amino acid residue is evolutionarily well conserved (Supplementary Table S3). Overall, not only does the cardiac phenotype of TNNT2-associated CM vary [6,[8][9][10], but the age at disease onset also shows a large range. Furthermore, the differences observed even in carriers of identical genetic variants suggest the influence of modifiers that promote the onset and development of a specific phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Bagnall et al 10 describe the outcomes of clinical genetic testing in a cohort of 221 unrelated children and young adults (≤18 years of age) with primary cardiomyopathy (HCM n=98, DCM n=89, RCM n=20, left ventricular noncompaction cardiomyopathy n=12, ACM n=2). Children with cardiomyopathy due to metabolic, mitochondrial, or overt syndromic causes were excluded.…”
Section: The Genetic Basis Of Childhood Cardiomyopathy Bagnall Et Almentioning
confidence: 99%